KONTRIBUSI DAYAH DARUL AZHAR DALAM PENERAPAN SYARIAT ISLAM DI KABUPATEN ACEH TENGGARA - Mahalli, Abd. Mukti, Edi Saputra (Program Studi Pendidikan Islam Pascasarjana UIN Sumatera Utara Medan, 2018)
Abstract :This study was aimed to (1) Describe the teaching curriculum of Dayah Darul Azhar Districtof Southeast Aceh, (2) Find its contribution in the implementation of Islamic Syari’at in Southeast Aceh,(3) To know the constraint factors in the implementation of Islamic Syari’at in Dayah Darul Azhar, SoutheastAceh. Theoretically, it could be used as the basis for the analysis of Dayah Darul Azhar’s contributionin the implementation of Islamic Syari’at particularly in Southeast Aceh and Indonesia in general which isbetter and relevant to the needs of the era. The selected research was qualitative. The results of this studywere special findings and discussion results. (1) Dayah educational curriculum in the implementationprocess of education becomes the absolute authority of its leadership. Regional Regulation Number 6 of2000 article 15 paragraph 2 mentions that the curriculum and teaching and learning activities in Dayahare arranged by its leader. Similarly, it is reinforced by Qanun no. 23 of 2002 article 23 which states thatthe curriculum and learning activities in Dayah is governed by its leader and or by its leadership colloquy.In Dayah Darul Azhar of Southeast Aceh, the curriculum used was the curriculum of the Ministry ofNational Education for general subjects, but for Dayah’s subjects it has its own curriculum that is byreferring to the Middle East level curriculum. (2) Dayah Darul Azhar’s contributions in the implementationof Islamic Syari’at in Southeast Aceh were of (a) to socialize Islamic Syari’at (learning curriculum, daakwah(propoganda) and preach and dress habit). (b) to guide the implementation of Islamic Syari’at (c) toinculcate and improve aqidah. (d) Tausiyah and the appeal. (3) The obstacle faced is the unavailability ofLanguage Lab, the lack of teachers from Middle East Graduate and the institution has not found thepattern of graduate about their interest and talent to continue their higher education. The opportunities forthe implementation of Islamic Sharia in Darul Azhar dayah as follows: (1) Separation of all Dayah DarulAzhar’s activities between men and women, (2) helding a punishment for those who violate the rules(included for of Islamic Sharia) and (3) The existence of Tahfiz al-Quran coaching as following from theprogram of Islamic Sharia Office.Penelitian ini bertujuan untuk (1) Mendeskripsikan kurikulum pembelajaran dayah Darul Azhar KabupatenAceh Tenggara, (2) Menemukan kontribusidayah Darul Azhar dalam pelaksanaan syariat Islam di AcehTenggara, (3) Mengetahui faktor-faktor kendala dalam pelaksanaan syariat Islam di dayah Darul AzharKabupaten Aceh Tenggara. Kegunaan Secara teoritis akan dapat dijadikan sebagai landasan analisaterhadap kontribusidayah Darul Azhar dalam pelaksanaan Syariat Islam di Aceh Tenggara khusunyadan Indonesia pada umumnya yang lebih baik dan relevan dengan kebutuhan zaman. Penelitian yang dipilih adalah kualitatif. Hasil penelitian ini merupakan temuan khusus dan hasil pembahasan. (1) Pembuatankurikulum pendidikan dayah dalam proses implementasi pendidikan menjadi wewenang mutlak pimpinandayah. Peraturan Daerah (Perda) Nomor 6 tahun 2000 Pasal 15 ayat 2 disebutkan bahwa kurikulum dankegiatan belajar mengajar di dayah diatur oleh pimpinan dayah yang bersangkutan dan Qanun No. 23Tahun 2002. Pasal 23 yang menyebutkan bahwa kurikulum dan kegiatan pembelajaran pada dayahdiatur oleh pimpinan dayah dan atau oleh musyawarah pimpinan dayah. Pada dayah Darul Azharkabupaten Aceh Tenggara, kurikulum yang digunakan adalah kurikulum Kementerian Pendidikan Nasionaluntuk mata pelajaran umum, sedangkan untuk mata pelajaran dayahnya memiliki kurikulum tersendiriyaitu dengan mengacu pada kurikulum Pendidikan setingkat Timur Tengah.. (2) Korntribusi dayah DarulAzhar dalam penerapan syariat islam di Kabupaten Aceh Tenggara berupa (a ) melakukan sosialisasisyariat islam (kurikulum pembelajaran, dakwah dan khutbah, dan kebiasaan berpakaian ). (b) mengawalpelaksanaan syariat islam. (c) menanamkan dan memperbaiki akidah. (d) Tausiyah dan seruan. (3)Kendala yang di hadapi berupa ketidaktersedianyaMa’mal Lukhah ( Lab Bahasa ), minimnya tenagapengajar dari alumni Timur Tengah dan belum menemukan pola minat dan bakat Alumni untuk melanjutkanPendidikan tinggi. Peluang penerapan Syariat islam di dayah Darul Azhar sebagai berikut: (1) Pemisahantempat semua kegiatan dayah antara laki-laki dan perempuan, (2) ‘Iqob bagi yang melanggar aturan dan(3) Adanya program Dinas Syariat Islam berupa pembinaan Hafiz.Kata Kunci: Kontribusi Daya, Penerapan Syariat Islam